B-Mode and Doppler Ultrasonography in a Murine Model of Ehrlich Solid Carcinoma With Different Growth Patterns - Castelló, Carla Martí; Miguel, Marina Pacheco; Silveira-Lacerda, Elisângela de Paula; Bakuzis, Andris Figueiroa; Borges, Naida Cristina (Frontiers in Oncology, 2020)
Ehrlich solid carcinoma (ESC) is one of the tumor models used in cancer research. Although it is widely used, it has no ultrasonographic descriptions. In this study, serial B-mode and Doppler ultrasonographic examinations were performed for 23 days for ESCs inoculated into 18 Swiss albino mice. The growth patterns were analyzed, and on the basis of their growth curve, the tumors were classified into two groups: fast growth (FG) and slow growth (SG). Ultrasonographic characteristics of the tumor’s capsule, margins, echogenicity, echotexture, vascular index (VI), distribution of vascular flow, and Doppler indices such as the resistive index, pulsatility index, and peak systolic velocity (SV) were analyzed and compared between the two groups. A high VI and earlier blood flow were noted in the FG group (p<0.05). Additionally, SV was higher in the FG group than in the SG group (13.28 ± 0.38 cm/s vs. 8.43 ± 0.26 cm/s). In contrast, a change in echogenicity and flow distribution patterns were observed, especially in FG tumors. Therefore, ESC presented with few ultrasonographic differences between FG and SG tumors, especially vascularization during the initial stages of tumor growth.